2016
DOI: 10.1371/journal.pone.0164835
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Pulmonary Function following 6 Months of Cigarette Exposure: Implications for Sexual Dimorphism in Mild COPD

Abstract: Female smokers have increased risk of chronic obstructive pulmonary disease (COPD) compared with male smokers who have a similar history of cigarette smoke exposure. We have shown previously that chronic smoke exposure for 6 months leads to increased airway wall remodeling in female C57BL/6 mice compared with male C57BL/6 mice. These differences, however, were not evident in female ovariectomized mice exposed to cigarette smoke. Herein, we report on the pulmonary function test results from the flexiVent system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
4
34
0
Order By: Relevance
“…We have previously demonstrated that female mice have increased airway wall thickness, lymphoid follicle expression, oxidative stress and distal airway resistance after chronic smoke exposure compared to male mice, and these effects were attenuated with ovariectomy [23,24,26]. To extend previous findings that showed chronic cigarette smoke exposure altered the murine gut microbiome [42], we have systemically investigated specific sex-related effects in the cecal microbiome of mice in response to chronic smoke exposure.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We have previously demonstrated that female mice have increased airway wall thickness, lymphoid follicle expression, oxidative stress and distal airway resistance after chronic smoke exposure compared to male mice, and these effects were attenuated with ovariectomy [23,24,26]. To extend previous findings that showed chronic cigarette smoke exposure altered the murine gut microbiome [42], we have systemically investigated specific sex-related effects in the cecal microbiome of mice in response to chronic smoke exposure.…”
Section: Discussionmentioning
confidence: 97%
“…The data reported in the present study were generated from mouse samples collected from a previous study where we examined the effect of sex-related differences on pulmonary function from chronic cigarette exposure [23]. In the current study, we report additional data focusing on the cecal microbiome and its contribution to changes in whole-body weight after chronic smoke exposure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smokeexposed groups were exposed to three cigarettes (one 1R1 and two 2R4F with the filters removed, or two 1R1 and one 2R4F with the filters removed on every other smoking day) per day for 5 days per week for 6 months. All smoke exposures were conducted using our standard nose-only smoke exposure system [5,14,15].…”
Section: Smoke Exposurementioning
confidence: 99%